Schleiermacher and the Transmission of Sin - Helen De Cruz; Johan De Smedt (TheoLogica, 2022)
Understanding the pervasiveness of sin is central to Christian theology. The question of why humans are so sinful given an omniscient, omnipotent, and omnibenevolent God presents a challenge and a puzzle. Here, we investigate Friedrich Schleiermacher’s biocultural evolutionary account of sin. We look at empirical evidence to support it and use the cultural Price equation to provide a naturalistic model of the transmission of sin. This model can help us understand how sin can be ubiquitous and unavoidable, even though it is not biologically transmitted, and even if there is no historical Fall that precipitated the tendency to sin.